Towards a paradigm on the value - Truong Hong Trinh (Cogent Economics & Finance, 2018)
This paper explores the value concept to understand the notions of value and price that form the base of value theories. Since value is more appreciate than utility in explaining value creation and value distribution in the today's society and economy, the theory of value is amended to conduct value creation and market behavior in the economy. From the theoretical base, the value added approach is used for GDP measurement that unifies with both the expenditure approach and the income approach. The study result indicates that there is a value balance between the firm and the customer, and the relationship between value balance and market equilibrium. The paper contributes a new paradigm on the value that provides a clearer understanding on value creation and market behavior in the economy.
Keywords: D24; D46; O40; 330; value concept; value creation; value balance; market equilibrium; market behavior